Factors Affecting Purchase Interest of Muslim Consumer on Online Platform - Imari, Iqbal; Haryadi, Imam (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
As the highest Muslim population in the world Indonesian has been reported contribute to millions of daily shopping transaction as majority of Muslim in Indonesia like any other groups in Indonesia are accessing online shop through internet and mobile apps. This study aimed to investigate the key factors that influence Muslim purchase interest on online platform in Indonesia. The method employs in this study are quantitative method with multiple regression analysis. To assess the validity of instruments pilot test has been conducted and to ensure the validity and reliability of the data, factor analysis using exploratory factor analysis and reliability test are utilized. Correlation test and collinearity test employed as well to ensure there are no mulitcollinearity issue in this study. Sample size in this study using Freedman et al., approach with data collection technique is simple random sampling. Based on the approach the sample size of this study is about 266. The data collected are about 300 yet the respondents that utilizing online shop are about 258. Hence, 258 data from respondents that are enable to analyze. The result shows that partially, price have a positive and significant effect on purchase interest as well as product quality show it positive and significant relationship with purchase interest. Simultaneously, both price and purchase interest have a significant relationship on Muslim purchase interest on online platform. Based on the R2 result, 48.3% of purchase interest variance are explained by price and product quality while the rest 51.7% are excluded from this study.